2020
DOI: 10.1155/2020/5478574
|View full text |Cite
|
Sign up to set email alerts
|

The New Biomarker for Cervical Squamous Cell Carcinoma and Endocervical Adenocarcinoma (CESC) Based on Public Database Mining

Abstract: To reconstruct the ceRNA biological network of cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC) and to select an appropriate mRNA as a biomarker that could be used for CESC early diagnosis and prognosis evaluation. We downloaded CESC data from the TCGA public database, and statistical analysis was conducted with the R software to find out differential expressed genes encoding for lncRNAs, miRNAs, and mRNAs. The differentially expressed mRNAs (DEmRNAs) screened in the ceRNA network were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…HCAR3 is a receptor for 3-OH-octanoid acid and a low affinity receptor for nicotinic acid, which mediates the negative feedback regulation of adipocyte lipolysis [ 13 ]. Previous studies reported that higher expression of HCAR3 was negatively correlated with survival time of cervical cancer patients [ 14 ]. In CRC patients, the average expression of HCAR3 was increased in CRC tissues compared to normal tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HCAR3 is a receptor for 3-OH-octanoid acid and a low affinity receptor for nicotinic acid, which mediates the negative feedback regulation of adipocyte lipolysis [ 13 ]. Previous studies reported that higher expression of HCAR3 was negatively correlated with survival time of cervical cancer patients [ 14 ]. In CRC patients, the average expression of HCAR3 was increased in CRC tissues compared to normal tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gynecological cancer is a serious threat to women’s health worldwide, especially cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), ovarian cancer (OV), uterine corpus endometrial carcinoma (UCEC), and uterine carcinosarcoma (UCS). Globally, CESC is the fourth most common female malignancy and the second-highest cause of female cancer-related deaths [ 1 , 2 ]. Human papillomavirus infection (HPV) is the main cause of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The modern methods are used to search for serum markers in cervical cancer by mean of perspective technologies such as magnetic bead-based weak cation-exchange chromatography fractionation combined with matrix-assisted laser desorption / ionization-time of flight mass spectrometry [100], the multiplex proximity extension assay is used [101]. A significant amount of modern research of cervical neoplasia is aimed at identifying genetic, epigenetic changes, revealing the possible role of long non-coding RNAs and circular RNAs in cervical carcinogenesis [102][103][104][105][106][107]. Modern tendencies in the problem of cervical neoplasia include research on immune factors and the vaginal microbiome [108][109][110].…”
Section: Discussionmentioning
confidence: 99%